Amniotic Fluid Embolism - Darshandhari, Gayatri (Journal of Nursing Education of Nepal, 2023)
Amniotic fluid embolism (AFE) is a devastating obstetric complication that requires early and  aggressive intervention with optimal cardiopulmonary resuscitation, as it has high morbidity and  mortality. Immediate recognition and diagnosis of AFE is essential to improve maternal and fetal  outcomes. The true incidence of this entity is unclear because this syndrome is difficult to identify  and the diagnosis remains one of exclusion, with possible under-reporting of nonfatal cases. AFE  is caused by abnormal activation of immunologic mechanisms following entry of fetal antigens  into maternal circulation. AFE classically presents as a sudden cardiovascular collapse associated  with respiratory compromise, fetal distress and development of a coagulopathy. Treatment of AFE  is supportive and directed at treating cardiovascular, pulmonary, and coagulation derangements.
Keywords: Amniotic Fluid, Embolism; Amniotic Fluid; Embolism